Electro-Optical Simulation Of In Ultra-Thin Photonic Crystal Amorphous Silicon Solar Cells - Merabti, Abdelhak; Bensliman, Abdelkader; Habab, Mahmoud (American International Journal of Multidisciplinary Scientific Research, 2019)
Hydrogenated amorphous Si (a-Si:H) is an important solar cell material. The critical problem in the a-Si:H-based photovoltaic cell is increasing the conversion efficiency. To overcome the difficulty, higher conversion efficiency demands a longer optical path to increase optical absorption. Thus, a light trapping structure is needed to obtain more efficient absorption. In this context, we propose a complete solar cell structure for which a 1D grating is etched into the ultrathin active absorbing layer of a one-dimensional "CP 1D" photonic crystal a-Si: H characterized by the optimal parameters: period a = 480 nm, a filling factor ff = 50% and a depth d = 150 nm. This was selected by varying the CP1D parameters to maximize the absorption integrated into the active layer. CP1D is suggested as an intermediate layer in the solar cell concentration system. This study allowed us to model the optical and electrical behavior of a CP1D solar cell. After optimization of the geometrical parameters (period and fill factor ... etc.), we concluded that the CP1D led to greater optical gains than for their unstructured equivalent. The simulation clearly illustrates that the electric field strongly affects the electro-optical characteristics of the devices studied, and that it is clear that 1D PC solar cells as active layer have exhibited a high electric field distribution. We have focused on the net on the effect of the active layer and its beneficial role in the sense of expressing the photovoltaic performance of the devices.